2020
DOI: 10.1371/journal.ppat.1008737
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between SARS-CoV-2 and the type I interferon response

Abstract: The severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) is responsible for the current COVID-19 pandemic. An unbalanced immune response, characterized by a weak production of type I interferons (IFN-Is) and an exacerbated release of proinflammatory cytokines, contributes to the severe forms of the disease. SARS-CoV-2 is genetically related to SARS-CoV and Middle East respiratory syndrome-related coronavirus (MERS-CoV), which caused outbreaks in 2003 and 2013, respectively. Although IFN treatment gave … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
465
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 443 publications
(503 citation statements)
references
References 162 publications
19
465
0
4
Order By: Relevance
“…Our analysis indicates that during a SARS-CoV-2 infection less cytokines than expected are released, autophagic turnover is blocked and general immune activation is perturbed. This is supported by a large amount of data from COVID19 patients [24][25][26][27][28]45,62,[71][72][73] . However, an important question remains: Why are some innate immune pathways, such as IFN-γ signaling less antagonized (Fig.…”
Section: Discussionmentioning
confidence: 70%
“…Our analysis indicates that during a SARS-CoV-2 infection less cytokines than expected are released, autophagic turnover is blocked and general immune activation is perturbed. This is supported by a large amount of data from COVID19 patients [24][25][26][27][28]45,62,[71][72][73] . However, an important question remains: Why are some innate immune pathways, such as IFN-γ signaling less antagonized (Fig.…”
Section: Discussionmentioning
confidence: 70%
“…Furthermore, under certain conditions, the interferon α-induced viperin converts up to 30% the cellular pool of CTP into ddhCTP, further increasing its stoichiometry and favoring its potency 30 . This may explain why SARS-CoV-2 viral proteins inhibits the interferon response 33 . ddhCTP therefore represents an exciting viral replication inhibitor with a low cytotoxicity and high efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Reports have suggested that SARS-CoV-2 infection is associated with an absent or delayed type I IFN response and an exacerbated release of proinflammatory cytokines [47]. It is known that the SARS-CoV-2 virus encodes at least 10 proteins that allow the virus to inhibit, evade, or counteract the effects of type I IFNs [48]. In a small study by Trouillet-Assant et al, Covid-19 patients who failed to produce a detectable type I IFN response were significantly more likely to require invasive ventilation [49].…”
Section: The Restorative Effects Of Vitamin D May Enhance Recovery Dumentioning
confidence: 99%